2023
DOI: 10.3390/ijms24021641
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-Mediated Timp1 Silencing Inhibited the Inflammatory Phenotype during Acute Lung Injury

Abstract: Acute lung injury is a complex cascade process that develops in response to various damaging factors, which can lead to acute respiratory distress syndrome. Within this study, based on bioinformatics reanalysis of available full-transcriptome data of acute lung injury induced in mice and humans by various factors, we selected a set of genes that could serve as good targets for suppressing inflammation in the lung tissue, evaluated their expression in the cells of different origins during LPS-induced inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 133 publications
(160 reference statements)
0
5
0
Order By: Relevance
“…Previously, we demonstrated the possibility of reducing the severity of acute injury in the lungs after intranasal instillation of anti-Timp1 siRNA complexed with cationic liposomes [35]. We showed that the reduction of inflammation was accompanied by a reduced number of neutrophils in the BAL fluid.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Previously, we demonstrated the possibility of reducing the severity of acute injury in the lungs after intranasal instillation of anti-Timp1 siRNA complexed with cationic liposomes [35]. We showed that the reduction of inflammation was accompanied by a reduced number of neutrophils in the BAL fluid.…”
Section: Discussionmentioning
confidence: 86%
“…The treatment of mice by anti-Il6 siRNA not only significantly changed the proportion of neutrophils in BAL but also reduced the absolute number of leukocytes compared with LPS-challenged mice, which was not achieved by the anti-Timp1 siRNA treatment. The relative change in inflammatory processes evaluated by histological scoring also showed positive trends: 2.5 and 3.2 folds for anti-Timp1 and anti-Il6 siRNAs, respectively [35]. However, these differences in therapy efficacy may also be due to the chosen targets as well as to different delivery methods and target cells.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Chernikov et al studied the efficiency of siRNA-mediated TIMP-1 silencing as an approach to reduce the inflammatory phenotype during ALI. The authors demonstrated that by dampening TIMP-1, inflammation was lessened and respiratory function was improved in an ALI experiment, pointing to the possibility that TIMP-1 manipulation could be a potential remedy for ARDS [95].…”
Section: Tissue Inhibitor Of Metalloproteinase-1 (Timp-1)mentioning
confidence: 99%